Modelo de referência para o desenvolvimento de órteses por manufatura aditiva de baixo custo - Poier, Paloma Hohmann (2020)
The Reference Model for the development of orthoses by low cost additive manufacturing (MRDOAM) was designed with the intention of facilitating decision making and equipping teams that wish to manufacture upper limb orthoses using low cost AM by extrusion of materials. It was organized to systematize the production process of orthoses by AM, noting that these are highly personalized products and with therapeutic objectives, therefore depending on the participation of experienced health professionals. In contrast, the model also points out analyzes and activities that should be conducted by designers with experience in 3D CAD scanning and modeling, print planning and post-processing. MRDOAM was built based on guiding principles extracted from literature review and analysis considered as of quality and good practices for the development of Assistive Technology, orthoses in general, orthoses by AM and Design for Additive Manufacturing. In addition, four wrist, hand and finger orthoses were produced for children with Cerebral Palsy with low-cost technologies of AM by extrusion of material in order to identify from the practical experience the information necessary to propose the model’s steps and tools. MRDOAM was composed with activities and instruments for the pre-development, development and post-development phases of low cost orthoses by extrusion of materials. Finally, the model and its instruments were evaluated by 17 experts regarding their suitability. There was approval greater than 80% in all aspects evaluated. The suggestions for improvements were analyzed for the final composition of the model.